2004
DOI: 10.1177/001698620404800307
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Mentoring to Increase Black Male Representation in Gifted Programs

Abstract: This article explores factors that affect the decision of gifted Black males to participate in gifted programs. Ford (1996) maintains that Black students often “choose” not to participate in gifted programs, and this choice contributes to their underrepresentation in gifted education. This choice to not participate in gifted programs is often based on social or external influences, particularly negative peer pressures, as well as internal or psychological issues, namely racial identity status. Given this persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 18 publications
0
52
0
2
Order By: Relevance
“…What is life like for Black males who are gifted and high achievers? Building upon the seminal work of Ford (1992Ford ( -2006) over the last decade on under-representation of Black students in gifted education, and that of Grantham (1998Grantham ( , 2004aGrantham ( , 2004b and Hébert (2002), it appears that social issues, including stereotypes and peer pressures, contribute to the low rates of Black students being recognized and formally identified as gifted. Stereotypes about Black males inhibit teachers and other educators from seeing strengths in these students (Ford, Harris, Tyson, & Frazier Trotman, 2002;Grantham, 1998;Steele, 2003).…”
Section: Identity and Self-perception Peer Pressures Social Injusticementioning
confidence: 99%
See 1 more Smart Citation
“…What is life like for Black males who are gifted and high achievers? Building upon the seminal work of Ford (1992Ford ( -2006) over the last decade on under-representation of Black students in gifted education, and that of Grantham (1998Grantham ( , 2004aGrantham ( , 2004b and Hébert (2002), it appears that social issues, including stereotypes and peer pressures, contribute to the low rates of Black students being recognized and formally identified as gifted. Stereotypes about Black males inhibit teachers and other educators from seeing strengths in these students (Ford, Harris, Tyson, & Frazier Trotman, 2002;Grantham, 1998;Steele, 2003).…”
Section: Identity and Self-perception Peer Pressures Social Injusticementioning
confidence: 99%
“…Hence, Black males are less likely to share their feeling and emotions, to disclose with teachers and others interested in their welfare (Bonner, 2001;Grantham, 1998Grantham, , 2004aGrantham, , 2004bHébert, 2002). To repeat, these youth may avoid institutions and activities that are considered "uncool"-schools, libraries, bookstores, museums, and churches.…”
mentioning
confidence: 99%
“…Not only do adults come to internalize pessimistic images of African American males, too many of these students learn to believe, emulate, and even reinforce the images imposed upon them (Grantham, 2004a(Grantham, , 2004bWhiting, in press). Ford and Harris (1996) and Ford (1996) studied gender differences between gifted Black males and females in grades 4-6; findings indicated that gifted Black males had lower grades, exerted less effort in school, were more interested in sports and being popular or socially accepted, and were more likely to succumb to accusations of acting White than Black females.…”
Section: Gender Considerationsmentioning
confidence: 99%
“…A mentor and role model may be helpful in advancing African American students in the pre-encounter and immersion-emersion stages into healthier stages of racial identity. A mentor and role model can also help gifted Black students in the higher racial identity stages to maintain their positive self-image (Grantham, 2004a(Grantham, , 2004bWhiting, 2006aWhiting, , 2006b). Mentors and role models can guide gifted African American students in several ways.…”
Section: Multicultural Counselingmentioning
confidence: 99%
See 1 more Smart Citation